The Oxford guide to international humanitarian law - Saul, Ben; Akande, Dapo (Oxford, United Kingdom : Oxford University Press, 2020)
"This [book] is intended as a practical yet sophisticated overview of the subject for professionals who are not necessarily IHL experts, but who work in field where IHL may be relevant ... It is intended to be more detailed and nuanced, and less descriptive, than some of the many introductory surveys or student textbooks on IHL which have proliferated in recent years, precisely as a result of the burgeoning interest in the practice of IHL in many conflicts and countries"--Page v.
History and Sources / Jean-Marie Henckaerts -- Classification of Armed Conflicts / Dapo Akande -- Temporal and Geographic Reach of International Humanitarian Law / Emily Crawford -- Domains of Warfare / Sarah McCosker -- Persons Covered by International Humanitarian Law : Main Categories / Lawrence Hill-Cawthorne -- Fundamental Guarantees / Robert McLaughlin -- International Humanitarian Law and the Conduct of Hostilities / Michael N. Schmitt -- Specifically Protected Persons and Objects / Robin Geiss and Christophe Paulussen -- Protection of the Natural Environment / Cymie R. Payne -- Methods of Warfare / Gloria Gaggioli and Nils Melzer -- Weapons / Stuart Casey-Maslen -- Detention in Armed Conflict / Jelena Pejic -- Occupation / Sylvain Vite -- Humanitarian Relief Operations / Eve Massingham and Kelisiana Thynne -- War Crimes / Robert Cryer -- Implementation of International Humanitarian Law / David Turns -- International Humanitarian Law and International Human Rights Law / Marco Sassoli -- Terrorism, Counter-Terrorism, and International Humanitarian Law / Ben Saul.
Includes bibliographical references and index.
Keywords: Humanitarian law; War (International law)